Book Reviews (Journal of Finance, 1991)
Book reviewed in this article: International Finance and Financial Policy . Edited by HANS R. STOLL. Futures Markets . By DANIEL R. SIEGEL and DIANE F. SIEGEL. Continuous‐Time Finance . By ROBERT C. MERTON. Managing Financial Risk . By CLIFFORD W. SMITH, JR., CHARLES W. SMITHSON, and D. SYKES WILFORD.